2010
DOI: 10.1186/gb-2010-11-1-r5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid chromosome territory relocation by nuclear motor activity in response to serum removal in primary human fibroblasts

Abstract: Nuclear myosin 1β-dependent repositioning of chromosome territories occurs within 15 minutes of serum starvation in human cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
208
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(217 citation statements)
references
References 68 publications
5
208
4
Order By: Relevance
“…7). This observation is in contrast to the dynamic changes in nuclear organization observed under stress response conditions (13,30,31), in which loci move in less time than is required for a cell cycle. The nuclear topology did not return to its prestress configuration until after release from a mitotic block, however (30).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…7). This observation is in contrast to the dynamic changes in nuclear organization observed under stress response conditions (13,30,31), in which loci move in less time than is required for a cell cycle. The nuclear topology did not return to its prestress configuration until after release from a mitotic block, however (30).…”
Section: Discussioncontrasting
confidence: 52%
“…S9). Previous investigators have suggested that mitosis is necessary for the repositioning of genes during differentiation (7,30,31,51). Our chimeric myotube strategy allowed us to directly test whether changes in lineage-specific nuclear topology are dependent on cell division.…”
Section: Cell Division Is Required For Establishing Changes In Nucleamentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore plausible that these biochemical properties of actin are utilized also within the nucleus. Indeed, actin and nuclear myosins have been implicated in the movement of individual gene loci upon transcription activation (14)(15)(16) and even in rearranging whole chromosomes within the nucleus (17). Furthermore, although the functional conformation of nuclear actin is still under debate (18,19), many of the nuclear actin related functions mentioned above are disrupted upon treatment of cells with drugs affecting actin polymerization (15,20,21), suggesting that actin polymerization plays a role also in the cell nucleus.…”
mentioning
confidence: 99%
“…Furthermore, radial positioning suggests that there might be a quantitative relationship between CT's gene density and CT's distance to nuclear center, according to the "spherical 1 Mb chromatin domain" model [29]. However, gene-poor chromosomes can move away from nuclear periphery in quiescent or senescent human fibroblasts [30,31].…”
Section: Models For Interphase Chromosome Positioningmentioning
confidence: 99%